2004
DOI: 10.1081/lebm-200032766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sinusoidal 0.5 mT Magnetic Field on Leukocyte Adherence Inhibition

Abstract: Exposure of T lymphocytes to an external 50 Hz and 0.5 mT magnetic field was investigated in vitro using leukocyte adherence inhibition (LAI) assay which is a measure of cell-mediated immunity. Adherence of T lymphocytes taken from healthy humans and from cancer patients before and after medical treatment is enhanced after 1 h exposure to the magnetic field. The experimental findings for the magnetic field 0.5 mT are compared with published data for 1 and 10 mT. The results are consistent with suggestions of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…We suggest that disturbances of the energy levels possibly resulting in serious pathologies might be caused by energy-consuming parasites, such as the lactate dehydrogenase (LDH) virus (or Riley virus, now classified as NAD 1.1.1.27 Oxidoreductase). Our extensive immunological study [33][34][35][36][37] revealed a response to the LDH virus antigen in (statistically) all cancer patients. However, establishing etiological role of a pathogen in chronic diseases with decades-lasting incubation period is difficult.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…We suggest that disturbances of the energy levels possibly resulting in serious pathologies might be caused by energy-consuming parasites, such as the lactate dehydrogenase (LDH) virus (or Riley virus, now classified as NAD 1.1.1.27 Oxidoreductase). Our extensive immunological study [33][34][35][36][37] revealed a response to the LDH virus antigen in (statistically) all cancer patients. However, establishing etiological role of a pathogen in chronic diseases with decades-lasting incubation period is difficult.…”
Section: Introductionmentioning
confidence: 86%
“…The LAI assay is a complex and tedious experimental method, and unequivocal results are conditioned by a high purity of antigens. Chemical and physical agents can affect the cell-mediated immunity response [34][35][36]. For example, magnetic field 0.5-10 mT decreases (increases) adherence of CD 4 Ly taken from healthy humans (cancer patients).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations